Perception of diagnosis on municipal solid waste of Ipameri-GO population - Vieira, M. C.; Pelosi, A. P.; Paula, M. S. P.; Silva, E. S.; Carneiro, U. (Scientific Electronic Archives, 2017)
The issue of disposal of municipal solid waste (MSW) generated in households in the cities, has sparked debates and demanded research papers in order to promote and disseminate the handling and packaging suitable for the trash. The way of handling these wastes and their disposal in the city of Ipameri-GO and destination that provides this population has caused serious inconvenience to the community. Therefore, this work aimed, through interviews with residents of different neighborhoods of Ipameri, identify problems related to the management of household waste and diagnose the level of perception of the subject population. It was observed in this study that the handling of the solid waste in Ipameri has proved inefficient further by a lack of public education policy and hence the environment, in which the lack of activity of the population. The population in theoretical and scientific knowledge is lacking, regardless of social and economic class, although empirically this same population, presents itself willing to perform the selective collection and recycling of solid waste. This fact raises larger government incentives and investments in educational policy so that we can develop a policy for Environmental Education (EE), to be fruitful and lasting.